Effect of oral gastric tube insertion during anesthesia induction on nausea and vomiting of adenotonsillectomized patients - Yoldashkhan, Mehryar; Nazemi, Leila; Zohari, Sima; Nasiri, Navideh (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Nausea and vomiting are from the most common complications of surgery during recovery. Adenotonsillectomy is a common surgery among children, which can be followed by some complications such as nausea, vomiting, bleeding, and even death in some cases. There are some medical and nonmedical remedies to decrease nausea and vomiting. A nonmedical therapeutic procedure is reduction of abdominal pressure using oral gastric tube. This study aims to assess effects of gastric tube insertion during anesthesia induction on nausea and vomiting of adenotonsillectomized patients. Materials and Methods: This study was a clinical trial on 72 adenotonsillectomised children aged 6 to 12 years old in Shahid Montazeri hospital of Najaf-Abad. Patients were randomly divided to two groups of case group (36 Children with oral gastric tube) and controls group (36 children without oral gastric tube). Anesthesia method for both groups was similar. Frequency of nausea and vomiting were measured during the 24 hours following adenotonsillectomy. Data was analyzed using SPSS 15 and Mannwhithney U, Chi square, Spearman, Friedman and wilcoxon tests. Findings: Two groups were not significantly different regarding their demographic characteristics such as age, sex and weight (p>0.05). Frequencies of nausea and vomiting were significantly lower in the intervention group comparing to the control group in the first 2 hours in recovery room as well as in the first 2, 6, and 14 hours of patient attendance in the postsurgical ward (P 0/05). Conclusion: This study showed that the use of oral gastric tube during anesthesia induction can reduce nausea and vomiting after adenotonsillectomy. Key words : Adenotonsillectomy, anesthesia induction, Nausea and vomiting, oral gastric tube. REFERENCES -Barash PG Cullen BF Stoelting RK (2009). Hand Book of Clinical Anesthesia, Sixth edition . Philadelphia. Lippincott Williams & Wilkins. -Chukudebelu O et al (2010). The effect of gastric decompression on postoperative nausea & emesis in pediatric tonsillectomy . International Journal of Pediatric Otorhinolaryngology. 74(4) 674-676 -Dulak SB (2006). Inserting an NG tube. RN. 69 (6) 24ac1-24ac4. -Fazel M et al (2007). The effect of dexamethasone on postoperative vomiting and oral intake after adenotonsillectomy. International Journal of Pediatric Otorinholaryngology . 71(8) 1235-8 -Garrett K et al (2003). Managing nausea and vomiting . Current Strategies. Critical Care Nursing. 23 (1) 31-50 -Garetz S et al (2008). Behavior cognition, and quality of life after adenotonsillectomy for children for pediatric sleepdisordered breathing:summery of the literature. Otolaryingology-Head And Neck Surgury. 138 (1) S19-26. Jahanbakhsh S Soltani GH Ziaeifar M (2006). [Dexamethasone effect on reducing postoperative nausea and vomiting tonsillectomy]. Journal of Birjand University of Medical Sciences. 13 (3) 25-27. (Persian) -Jones JE et al (2001). Efficacy of gastric aspiration in reducing post tonsillectomy vomiting. Archive of Otolaryngology Head and Neck Surgery. 127 (8) 980-4. Miller R et al (2010). Millers Anesthesia , 7th edition. United States of America,Churchill Livingstone -Naseri K et al (2006). [Effect of acupressure on nausea and vomiting after orthopedic surgery]. Medical Journal of Hormuzgan Univesity. 10 (4) 357-362. (Persian) -Otchy P et al (1995). Dose the avoidance of nasogastric decompression following elective abdominal colorectal surgery affect the incidence of incisional hernia? Results of a prospective, randomized trial. Disease of the Colon &Rectum 38(6) 604-608 -Payani N et al (2009). [Compare of the efficacy of ondansetron with dexamethasone and metoclopramide and control nausea and vomiting following surgery adenotonsillectomy]. Journal of Medical Council of Islamic Republic Iran. 27(4) 456-463. (Persian) -Quinn F et al (2002). The tonsils and adenoids in pediatric patient. Grand Rounds Presentation, [on line] http://www.utmb.edu/otoref/grnds/Pedi-TA-020619/Pedi-TA-020619.htm .